FRACTIONATION OF PROTEASES FROM COWTAIL RAY (Trygon sephen) VISCERA USING POLYACRYLIC ACIDS - Achmad Poernomo (Indonesian Fisheries Research Journal, 1999)
Fractionation of proteases of cowtail ray (Tfygort, st;plwn) viscera using polyacrylic acids has been investigated.